Internal faults in stator winding of synchronous generator: Modelling, detecting and protecting - Amir Hossein Rezaei; Milad Beikbabaei; Moein Abedini; Mahdi Davarpanah (IET Generation, Transmission & Distribution)
Abstract Protection of synchronous generators (SGs) against internal faults, such as stator earth fault (SEF) and turn‐to‐turn fault (TTF), is crucial for ensuring the stability and security of the power system. This paper presents a phase domain model for simulating SEF and TTF in SGs, requiring only nameplate data and avoiding the need for complex geometric data or lengthy simulations typical of FEM models. The stator winding is divided into three sections, allowing for the calculation of magnetic field distribution in both healthy and faulty conditions. The model is capable of simulating short‐circuit turns at various locations within the stator winding with high accuracy and speed. The dynamic response of the generator is also incorporated into the model. The model's accuracy is validated through comparison with results from multiphysics simulation software. Furthermore, this study addresses the limitations of conventional protection methods in detecting TTF and proposes a novel, simple, fast, and accurate protection logic that can be implemented in digital protection relays and is effective across a wide range of TTF scenarios.